Expression of umami‐taste‐related genes in the tongue: a pilot study for genetic taste diagnosis. (30th June 2015) - Shoji, N; Kaneta, N; Satoh‐Kuriwada, S; Tsuchiya, M; Hashimoto, N; Uneyama, H; Kawai, M; Sasano, T
<x xml:space="preserve">Abstract</x> Objective Expression of taste‐related genes in the tongue was analysed to develop a technique for genetic diagnosis of umami taste disorders. Materials and methods Tissue samples were collected from healthy volunteers by scraping the foliate papillae of the tongue. Immunocytochemistry staining of gustducin, a taste‐cell‐specific G protein, and gene expression analysis by real‐time polymerase chain reaction of β‐actin, gustducin (GNAT3) and umami receptors (T1R1, T1R3 and mGluR1) were performed. Changes in umami receptor expression following application of umami substances onto the tongue were analysed. Results Gustducin‐positive cells were observed in the samples, indicating the presence of taste cells. Gene expression of β‐actin, GNAT3, T1R1 and T1R3 was detected in all seven samples tested, while that of mGluR1 was detected in four samples. Sequence analysis by NCBI Blast showed that each polymerase chain reaction product had a 99% rate of identification of its target sequence. Stimulation of the tongue with monosodium glutamate significantly upregulated the gene expression levels of T1R1 and T1R3, indicating that this method can detect alterations in umami‐related gene expression. Conclusion Evaluation of the expression of the umami receptor genes, T1R1 and T1R3, in the tongue may be clinically useful for objective genetic diagnosis of umami taste disorders.